General geology and joint analysis of Kampung Batu Mengkebang, Kuala Krai Kelantan - Nurzafirah Abd Halim (2017)
This research provides a study of joint analysis of the study area which are located at the centre state of Kelantan in the north east of Malaysia. This research focused to joint analysis. This research have done because before this, there is no data details, information and reference about the geological study of this area. The objectives of this research are to produce geological map of the study area, to identify the joint structure of the study area and to analyse the dynamic and kinematic aspect of the joint structure in the study area. Geological mapping was conducted to determine general geology of the area. The study of joint analysis was proceeds through morphological, stratigraphic and structural observation on study area. There is a three types of rock that exist in the study area which are igneous rock, sedimentary rock and metamorphic rock. The rock that have been found in the study area are ignimbrite, hornfel, claystone, pyroclastic and schist. The oldest rock is schist. The youngest lithology is the intrusion of ignimbrite. Then data collection was processed in laboratory works and analyses to get the result of the research. The result of joint analysis was shown based on Rose diagram and the maximum force direction in study area also have been identified and it is almost NE-SW direction.